Effects of TNFα on Dynamic Cytosolic Ca2 + and Force Responses to Muscarinic Stimulation in Airway Smooth Muscle - Han, Young-Soo; Delmotte, Philippe; Sieck, Gary C. (Frontiers in Physiology, 2021)
Previously, we reported that in airway smooth muscle (ASM), the cytosolic Ca2+ ([Ca2+]cyt) and force response induced by ACh are increased by exposure to the pro-inflammatory cytokine tumor necrosis factor a (TNFa). The increase in ASM force induced by TNF was not associated with an increase in regulatory myosin light chain (rMLC20) phosphorylation but was associated with an increase in contractile protein (actin and myosin) concentration and an enhancement of Ca2+ dependent actin polymerization. The sensitivity of ASM force generation to elevated [Ca2+]cyt (Ca2+ sensitivity) is dynamic involving both the shorter-term canonical calmodulin-myosin light chain kinase (MLCK) signaling cascade that regulates rMLC20 phosphorylation and cross-bridge recruitment as well as the longer term regulation of actin polymerization that regulates contractile unit recruitment and actin tethering to the cortical cytoskeleton. In this study, we simultaneously measured [Ca2+]cyt and force responses to ACh and explored the impact of 24-h TNFa on the dynamic relationship between [Ca2+]cyt and force responses. The temporal delay between the onset of [Ca2+]cyt and force responses was not affected by TNFa. Similarly, the rates of rise of [Ca2+]cyt and force responses were not affected by TNFa. The absence of an impact of TNFa on the short delay relationships between [Ca2+]cyt and force was consistent with the absence of an effect of [Ca2+]cyt and force on rMLC20 phosphorylation. However, the integral of the phase-loop plot of [Ca2+]cyt and force increased with TNFa, consistent with an impact on actin polymerization and, contractile unit recruitment and actin tethering to the cortical cytoskeleton.